(untitled) (Revista Ciência Agronômica, 2015)
The aim of this study was to evaluate differences between maize genotypes in relation to the germination response of the seeds and the growth of seedlings inoculated with Azospirillum brasilense, as well as the effect of inoculation on nitrogen levels and the chlorophyll content index of the leaves. The physiological seeds quality from the single-cross hybrids AG7098 and 2B707, and from the experimental synthetic varieties V2 and V4, inoculated with A. brasilense, was tested for germination, percentage and rate of emergence, and dry matter weight of the shoots and roots. Nitrogen levels and chlorophyll content index were evaluated in leaves of the same four genotypes grown in a greenhouse under different nitrogen supply systems and methods of inoculation with A. brasilense. The genotypes differ with regard to inoculation with A. brasilense. The hybrids were responsive to inoculation with A. brasilense for root dry matter weight. The V2 variety had a lower performance as regards root dry matter weight, with the opposite being seen for the dry matter weight of the shoots. V4 displayed no significant differences when inoculated. The results of the chlorophyll content index were not significant. Each genotype under evaluation displayed a different response for leaf nitrogen levels. It is possible to infer that the hybrids responded better to inoculation with the bacteria, with the greater root development leading to a better utilisation of water and nutrients.